2022
DOI: 10.3390/ijerph192416996
|View full text |Cite
|
Sign up to set email alerts
|

Higher Infection Risk among Health Care Workers and Lower Risk among Smokers Persistent across SARS-CoV-2 Waves—Longitudinal Results from the Population-Based TiKoCo Seroprevalence Study

Abstract: SARS-CoV-2 seroprevalence was reported as substantially increased in medical personnel and decreased in smokers after the first wave in spring 2020, including in our population-based Tirschenreuth Study (TiKoCo). However, it is unclear whether these associations were limited to the early pandemic and whether the decrease in smokers was due to reduced infection or antibody response. We evaluated the association of occupation and smoking with period-specific seropositivity: for the first wave until July 2020 (ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…The risk factor analysis showed that HCWs had an increased risk of infection compared to the general population, which is interestingly consistent with previous research on the KoCo19 cohort and other studies that have identified HCWs as a vulnerable group for infection [ 30 , 44 , 54 ]. However, the use of PPE has been shown to reduce the risk of infection [ 44 ], possibly leading to a change in the risk of infection in HCWs over time.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The risk factor analysis showed that HCWs had an increased risk of infection compared to the general population, which is interestingly consistent with previous research on the KoCo19 cohort and other studies that have identified HCWs as a vulnerable group for infection [ 30 , 44 , 54 ]. However, the use of PPE has been shown to reduce the risk of infection [ 44 ], possibly leading to a change in the risk of infection in HCWs over time.…”
Section: Discussionsupporting
confidence: 89%
“…However, the lower risk of infection among current smokers aligns with similar findings from the analysis of the KoCo19 cohort [ 30 ]. Additionally, a recent study by Günther et al (2022) supports these findings, as it demonstrated that current smokers were nearly half as likely to test positive for SARS-CoV-2 antibodies compared to non-smokers [ 54 ]. That study did not observe any differences in antibody levels between smokers and non-smokers who had been infected with or vaccinated against SARS-CoV-2, suggesting that the lower prevalence of antibodies in smokers may be attributed to lower infection rates rather than reduced antibody response.…”
Section: Discussionmentioning
confidence: 92%
“…The inverse association between smoking and SARS-CoV-2 seropositivity appears counter-intuitive because smoking impairs the immune system and increases the risk of several types of pneumonia ( 20 ). However, several other serologic studies have found that SARS-CoV-2 infection is less in smokers ( 21 25 ). Smoking is known to cause inflammation in airways.…”
Section: Discussionmentioning
confidence: 89%
“…This indicates that the combination of vaccination and a vigorous use of PPE is capable to prevent the vast majority of SARS-CoV-2 infections and to provide considerable safety to HCW. Nevertheless, recent findings indicate that HCW still remain at an increased risk of infection compared to the average population [ 1 ], which underlines the ongoing discussion on the impact of occupational versus non-clinical and private SARS-CoV-2 infection risks [ 30 ]. The broad definition of high-risk activities contrasts with rather low infection rates prior to vaccination and challenges the comparability of the contact situations described in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, health care workers (HCW) engaged in direct patient care were regularly exposed to severe-acute-respiratory-syndrome-coronavirus 2 (SARS-CoV-2) [ 1 ]. To ensure the safety of HCW and to maintain patient care at the University Hospital of Erlangen (UKER), a tertiary-care hospital in Bavaria, various protective measures were immediately introduced during the first wave of SARS-CoV-2 infections in Germany.…”
Section: Introductionmentioning
confidence: 99%